Students' Self-assessed Competence Levels During Nursing Education Continuum - A Cross-sectional Survey - Kajander-Unkuri Satu; Meretoja Riitta; Katajisto Jouko; Leino-Kilpi Helena; Suikkala Arja (De Gruyter, 2025)
During nursing education, nursing students are required to develop their competence to be able to fulfill their duties safely as Registered Nurses. The aims of this study were to explore 1) nursing students' self-assessed competence levels during education 2) the relationship with competence and frequency at which competencies are utilized in clinical practice, and 3) factors related to competence levels. 841 (response rate 67.6 %) nursing students responded to the Nurse Competence Scale in a cross-sectional study. The self-assessed overall competence levels were improving during the education continuum (VAS-means 1st 56.6; 2nd 58.3; 3rd 59.8 and 3.5th -year students 68.4). Every group revealed a significant positive correlation with competence and frequency at which competencies are utilized in clinical practice in clinical placement. Risk factors for low competence were also identified. Systematic multimethod competence evaluations with longitudinal designs are needed to monitor outcomes of nursing education.